AB0562 Male versus Female Patients with Primary SjÖGren's Syndrome: A Comparison of Ethnicity, Clinical Features, Serology and Outcome in 156 Patients – is There a Male SjÖGren's Phenotype?. (10th June 2014) - Tung Chen, Y.; Isenberg, D.; Abrol, E.
Abstract : Background: There are conflicting data from previous studies as to whether a male Sjögren's phenotype really exists. We have taken advantage of our own Sjögren's cohort (n=156) followed up for 27 years to re-examine this question. Objectives: To review any differences between male and female patients with primary Sjögren's Syndrome (pSS) with respect to clinical features, serology and outcome in our cohort followed for up to twenty-seven years. Methods: Using the American European Consensus Group classification criteria for Sjögren's Syndrome, 156 patients seen at University College of London Hospital were identified between 1986 and November 2013. We analysed demographic, clinical and serological data, as well as outcome using SPSS v19.0 software. Comparisons between continuous variables were made using the Kruskal–Wallis test and Chi-square test or Fisher's exact two-tailed test were used for categorical variables when it was appropriate. Results: A total of 156 patients were identified and followed up between 1986 and 2013, 142 females (91%) and 14 males (9%), a female to male ratio of 9:1, and similar mean age at diagnosis (54, 3 years, SD 13.6; p=0, 579). 125 females (88%) were Caucasian vs 10 males (71%) and 7 were Afro-Caribbean (5%) vs 0, although, the differences were not significant (p=0, 098 and p=0, 395). However, we found a higher prevalence of Asian SS males (4 (29%) vs 10 (7%); p=0, 024). There were no differences (male vs female) in the presence of arthritis (20% vs. 21%; p=0, 878), neurological involvement (26% vs 28%; p=0, 761), oral ulcers (10% vs 14%; p=639), Raynaud's syndrome (31% vs 29%; p=0, 852), lung interstitial fibrosis (19% vs 14%; p=664), hemopathy (57% vs 57%; p=0, 694), gastrointestinal autoimmune diseases (13% vs 14%; p=0, 925), malignancy (24% vs 43%; p=0, 302), fatigue (49% vs 50%; p=0, 920), lymphadenopathy (10% vs 14%; p=0, 640), hypertension (8% vs 7%; p=0, 936) or thyroidopathy (8% vs 7%; p=0, 866). Compered to female, no man developed vasculitides (9%; p=0, 609), rash (10%; p=0, 617), parotidomegaly (15%; p=0, 218) or infection (11%; p=0, 364). In both groups there were similar presence of anti-Ro antibodies (50% vs 57%; p=0, 612), anti-La antibodies (35% vs 42%; p=0, 569), anti-RNP antibodies (5% vs 0%; p=0, 396), the mean titre of RF (1:640, SE 1:74; p=0, 519) and ANA (1:320, SE 1:36; p=0, 990). There were no differences in survival rate (58% vs 43%; p=0, 284); the main cause of death was malignancy and cardiac disease (12% vs 17%; p=0, 652). A high incidence of malignancy (24% vs 43%; p=0, 302), hemopathy (57%; p=0, 694) and additional autoimmune diseases (41% vs 29%; p=0, 371) was observed. Conclusions: In our cohort, we find a significant higher prevalence of pSS in Asian male than female patients, however, although a trend could be observed, we did not find differences in clinical and serological features or outcome. Thus, we have not been able to identify a particular male Sjögren's phenotype. However, it is possible that the modest number of the males with pSS contribute to the lack of statistical difference between the two groups. It may be that a much larger group of men with pSS is needed to reach a consensus. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1265